Probability Cueing Influences Miss Rate and Decision Criterion in Visual Searches. (May 2014) - Ishibashi, Kazuya; Kita, Shinichi
In visual search tasks, the ratio of target-present to target-absent trials has an important effect on miss rates. The low prevalence effect indicates that we are more likely to miss a target when it occurs rarely rather than frequently. In this study, we examined whether probability cueing modulates the miss rate and the observer's criterion. The results indicated that probability cueing affects miss rates, the average observer's criterion, and reaction time for target-absent trials. These results clearly demonstrate that probability cueing modulates two parameters (i.e., the decision criterion and the quitting threshold) and produces a low prevalence effect. Taken together, the current study and previous studies suggest that the miss rate is not just affected by global prevalence; it is also affected by probability cueing.